A Dispute of Chinese Avant-Garde Theoreticians Wang Naming and Gao Minglu about Three Types of Zhang Yanyuan’s Pictorial Forms - Belozerova, Vera G. (Actual Problems of Theory and History of Art, 2022)
Wang Naming (born 1962) is a famous Chinese avant-garde calligrapher who created the “combination of balls with hieroglyphs” (zi qiu zuhe) style in the 1990s. He is now considered to be the most competent critic, most experienced and successful curator of contemporary Chinese art. Wang Naming has written ten fundamental monographs on the theory of avant-garde calligraphy. Gao Minglu (born 1949) became famous as an avant-garde artist, a major theoretician and critic of modern art. In his numerous monographs, he elaborates the “Direction of Design” (Yi pai) theory. Both experts find the origins of the avant-garde art theory in the treatise by Zhang Yanyuan (815–907) “Records of Famous Artists of Different Eras” (Lidai ming hua ji), which refers to three types of “visual fixations”(tu zai): “depiction of principles” (tu li) i.e. trigrams; “depiction of knowledge” (tu shi), i.e. hieroglyphic writing; and “depiction of forms” (tu xing), i.e. painting. Gao Minglu interprets Zhang Yanyuan’s typology by analogy with abstractionism, conceptualism, and realism in Western art, which Wang Naming strongly disagrees with, arguing against the mechanical transfer of traditional Chinese aesthetic categories to the Western culture space.
Keywords: art theory; contemporary Chinese art; Chinese calligraphy; Gao Minglu; gong bi; Wang Naming; wenrenhua; Zhang Yanyuan